Combustion characteristics of Al/B loaded Gel fuel droplets under high temperature and pressure - Mengxiong Li; Chuxiang Sun; Qingyu Li; Qingchun Yang; Hongxin Wang; Xu Xu (Fuel Processing Technology, 2025)
This research investigates the combustion behavior of aluminum and boron loaded gel fuel droplets (10–20 wt%) under high-temperature and high-pressure conditions. High-speed and color imaging captured the combustion process. The addition of gellant induces micro-explosions that enhance the burning rate; however, increasing particle concentration weakens this effect. At high concentrations, early particle shell formation hinders gel layer development, suppressing micro-explosions. Both micro-explosions and particle shells promote liquid-phase combustion. At low concentrations, micro-explosions dominate the enhancement, while at high concentrations, larger, early-formed particle shells are the primary contributor. Increasing ambient pressure reduces micro-explosion intensity but shortens ignition delay and raises the burning rate. Under high pressure, weak micro-explosions offer less enhancement and lead to larger particle agglomerates. Aluminum and boron gel droplets show similar liquid-phase behavior, but differ in particle combustion: aluminum ignites under all conditions, while boron requires higher pressures. The combustion process of high-concentration gel droplets under elevated conditions is divided into four stages: Stable Combustion, Particle Shell Formation, Particle Agglomerate Ignition, and Molten Particle Combustion. This staged model emphasizes the dominant role of particle shells, with minor contributions from micro-explosions.